The facilitation of the client or customers value generation through digitalization: a study on mobile financial service provider bKash - Alvi, Nagib Mahfuz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.